2017
DOI: 10.1097/mao.0000000000001322
|View full text |Cite
|
Sign up to set email alerts
|

Performance Plateau in Prelingually and Postlingually Deafened Adult Cochlear Implant Recipients

Abstract: Adults with postlingual deafness undergoing unilateral CI show significant improvement in speech perception for 3 years postimplantation, at which point their performance continues to improve, albeit at a flatter rate. The performance of adults with prelingual deafness improves significantly as late as 5 years postimplantation. These time intervals reflect a change to the currently reported 6 to 12 months period and should impact on counseling, especially in the prelingual CI candidate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
46
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 8 publications
11
46
0
1
Order By: Relevance
“…The mean improvement from baseline to 6 months post activation was 54% in quiet and 40% in noise. These results are comparable to studies that used the same sentence materials and presentation levels in adult CI users [11][12][13]. Of course, comparisons between studies should be done with caution given the large interindividual variability in CI outcomes as well as methodological differences.…”
Section: Clinical Efficacysupporting
confidence: 69%
See 3 more Smart Citations
“…The mean improvement from baseline to 6 months post activation was 54% in quiet and 40% in noise. These results are comparable to studies that used the same sentence materials and presentation levels in adult CI users [11][12][13]. Of course, comparisons between studies should be done with caution given the large interindividual variability in CI outcomes as well as methodological differences.…”
Section: Clinical Efficacysupporting
confidence: 69%
“…As expected, HINT performance typically increases considerably after CI activation; for how long the performance continues to improve post-activation before reaching a plateau is variable but is most likely to be at least 1 year [11,12]. One year after activation, typical scores of adults with postlingual deafness tested in a CI-only condition with English HINT sentences presented at 60 dB SPL range from 69 to 74% in quiet [12,13,13] and from 54 to 61% in 70 dB noise, equivalent to a + 10 dB signal-to-noise ratio (SNR) [11,13]. In the Zwolan et al study [13], HINT sentences were presented from the front (0-degree azimuth) and speechshaped noise was presented from the CI side (90-degree or 270-degree azimuth), while the Cusumano et al study [11] presented both sentences and speech from the front.…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…Runge et al reported a mean 12‐month unilateral CNC word score of 52.9% in a group of 38 postlingually deafened adults with a traditional long electrode array. Cusumano et al completed a retrospective review of outcomes in pre‐ and postlingually deafened adults. For the 102 postlingually deafened adults, the mean 12‐month CNC word score was 57.6%.…”
Section: Discussionmentioning
confidence: 99%